Sir Francis Galton's Philosophy of Measurement Science and Its Relevance for the Development of the Psychometric Paradigm: Filsafat Ilmu Pengukuran Sir Francis Galton dan Relevansinya bagi Pengembangan Paradigma Psikometri - Nugraha, Dwi Yan; Kuswanjono, Arqom (Jurnal Filsafat Indonesia, 2024)
This article discusses the origins of the psychometric paradigm and its reliance on the notion that mental attributes can be measured. Galton's assumption that mental attributes can be discerned through definite actions in response to definite situations is misguided. This article highlights the ternary nature of causality, involving causes, effects, and specific causal fields. The same cause may not produce the same effect in different causal fields, and different causes may produce the same effect in different causal fields. The relationships between observable measures and aspects of character are unclear, and indirect indices of mental attributes are inherently ambiguous. This article focuses on Francis Galton's role in establishing these beliefs and argues that his reasoning was flawed and influenced by Pythagoras' philosophy of science and his desire to present eugenics as science. This paper aims to describe Sir Francis Galton's theory regarding the science of measurement and its relevance to psychometrics. Using the literature review method on various sources (scientific articles and textbooks) related to the topic of discussion. Overall, this article challenges the assumption that mental attributes are inherently quantitative and  argues  for  a  more  nuanced understanding of  measurement in psychometrics.